2004
DOI: 10.1590/s1516-635x2004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Performance and color of broilers fed diets containing Rhodocyclus gelatinosus biomass

Abstract: The objective of this study was to evaluate the effect of different supplementation levels of Rhodocyclus gelatinosus biomass on the performance and pigmentation of broilers. Cobb broilers were raised in pens and were fed a sorghum-based diet until 35 days of age. At the 36th day of age, ninety-six birds were randomly distributed to four treatments consisting of experimental diets with different supplementation levels of Rhodocyclus gelatinosus biomass (0, 75, 150 and 300 ppm) added to the finisher basal diet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 10 publications
2
12
0
1
Order By: Relevance
“…Phototrophic bacteria are effective as animal feed. 56 The key restriction for microbial food/feed production from wastewater is potential contamination of the product for instance with pathogens. Only in specific cases such as food processing wastewater is there a case for direct-contact assimilation from wastewater.…”
Section: ■ Conventional Vs Direct Reuse: Up-cycling Nitrogen By a Shomentioning
confidence: 99%
“…Phototrophic bacteria are effective as animal feed. 56 The key restriction for microbial food/feed production from wastewater is potential contamination of the product for instance with pathogens. Only in specific cases such as food processing wastewater is there a case for direct-contact assimilation from wastewater.…”
Section: ■ Conventional Vs Direct Reuse: Up-cycling Nitrogen By a Shomentioning
confidence: 99%
“…People often associate strong colors of a food item to safety and health and so look for strongly pigmented products. Taking it into account, Ponsano et al (2002bPonsano et al ( , 2004a added Rhodocyclus gelatinosus biomass produced in poultry slaughterhouse wastewater in broilers rations and found an increase in the color of breast meat. Polonio et al (2010) used different concentrations of the same product in hens rations and found an improvement in yolks color, with no deleterious effects on birds performance.…”
Section: Physicochemical Parameter Quantitymentioning
confidence: 99%
“…Visual appearance, especially color, is the most important characteristic of foods and determines the choice or rejection of the product by the consumer (Ponsano et al 2004). Bright yellow color is an important demand by consumers for bulgur (Bayram 2005), pasta (Schulthess et al 2013;Zhang and Hamaker 2012), noodle (Hatcher et al 2008;Ito et al 2007), and semolina (Fratianni et al 2005;.…”
Section: Introductionmentioning
confidence: 99%